The stiff leg syndrome. - Brown, P; Rothwell, J; Marsden, C (1997)
Four patients had a chronic progressive disorder beginning in middle age and involving stiffness and painful spasms of the lower limbs. Spasms were spontaneous, reflex, and induced by voluntary movement. Patients had rigidity and abnormal postures of one or both legs. There was no truncal rigidity or exaggerated lumbar lordosis. Despite the presence of symptoms for up to 16 years, symptoms and signs of brainstem, pyramidal, and sensory dysfunction were absent. Sphincter disturbance developed after many years in one patient. Extensive investigation, including imaging of the whole neuroaxis, failed to disclose a cause. Anti-GAD antibodies were absent. Baclofen and diazepam led to some reduction in the painful spasms, but patients remained disabled by the condition. There were four core electrophysiological features. (1) Continuous motor unit activity was present at rest in at least one limb muscle. (2) Spasms tended to involve the repetitive grouped discharge of motor units. (3) Cutaneomuscular reflexes were abnormal. (4) There was little or no electrophysiological evidence of long tract disturbance. The patients form a characteristic syndrome, separate from the stiff man syndrome, and distinguishable from encephalomyelitis with rigidity. It is suggested that the condition is due to a chronic spinal interneuronitis.